Unusual Case of Bilateral Tubercular Mastitis - Gupta, Archit (Cureus, 2017)
Bilateral involvement of the breast with tuberculosis is extremely rare. It most commonly affects young lactating multiparous females, although rarely it may be reported in prepubescent males also. We present a case of a 27-year-old nulliparous female who presented with a history of multiple pus discharging sinuses around both areolae and was diagnosed as a case of bilateral tubercular mastitis. Tubercular mastitis being a paucibacillary disease, diagnosis is often difficult. Treatment consists of antitubercular therapy with or without surgery.​